Minimally Invasive Embedding of Saturated MSU Induces Persistent Gouty Arthritis in Modified Rat Model. (9th June 2021) - Xu, Han-Lin; Li, Sheng-Kun; Xue, Xiao-Ao; Chen, Zi-Yi; Hua, Ying-Hui
Abstract : Introduction. Animal models are valid for in vivo research on the pathophysiological process and drug screening of gout arthritis. Intra-articular injection of monosodium urate (MSU) is the most common method, while stable MSU deposition enveloped by inflammatory cells was rarely reported. Objective . To develop a modified gouty arthritis rat model characterized by intra-articular MSU deposition and continuous joint pain with a minimally invasive method. Method . A total of twenty-four rats were randomly allocated into six groups. Three intervention groups of rats received intra-articular MSU embedment. Sham groups received pseudosurgeries with equal normal saline (NS). Gross parameters and pathological features of synovium harvested from anterior capsule were estimated. Mechanical pain threshold tests were conducted over a 96-hour period postoperatively. Moreover, quantitative immunofluorescence was conducted to assess tissue inflammation. Result . After MSU embedding, rats got more persistent arthritic symptoms as well as tissue MSU deposition. More significant synovial swelling was detected in the MSU group compared to sham groups (P < 0.025 ). Behavioral tests showed that the embedding of MSU resulted in prolonged mechanical hyperalgesia during 2 hours to 96 hours postoperatively (P < 0.05 ). MSU depositions enveloped by inflammatory cells that express IL-1 β and TNF- α were detected in embedding groups. Quantitative immunofluorescence suggested that the frequencies of MSU interventions upregulated expression of proinflammatory factors including IL-1 β and TNF- α (P < 0.05 ). Conclusion . A minimally invasive method was developed to establish modified rat model of intra-articular MSU deposition. This model was proved to be a simple reproducible method to mimic the pathological characteristics of persistent gouty arthritis.